Effects of the thermal treatment on structural and luminescence properties of Er3+-doped aluminophosphosilicate glasses obtained by the sol-gel method - Costa, Beatriz H. [UNESP]; Tayama, Gabriel T.; Rivera, V. A.G.; Messaddeq, Younès [UNESP]; Santagneli, Silvia H. [UNESP] (Elsevier, 2025)
Transparent glasses were prepared by vacuum heat-treating erbium-doped aluminophosphosilicate gels prepared using the sol-gel method. The evolution of thematerials structure with heat-treatment was studied by multinuclear solid-state NMR, Infrared and Raman spectroscopies, X-ray diffraction and SEM microscopy. The optical properties of the resulting materials were assessed by UV–Vis–NIR spectroscopy and luminescence of Er3+ ions. Our results showed that the heat treatment under vacuum led to a dense matrix, with an interconnected silicate network through Si-O-Si, Si-O-P and Al-O-P bonds, allowing the formation of different chemical environments for the Er3+ ions. Furthermore, heat treatment under vacuum resulted in a remarkable decrease in OH groups, leading to a 180-fold increase in luminescence intensity and FWHM values of around 100 nm for the sample doped with 0.5 mol.% Er3+. This new approach offers a novel way for fabricating homogeneous transparent glasses with a wide composition range, doped with rare earth elements, yielding the development of new optical devices for telecommunications with broadband NIR emission.
Keywords: Aluminophosphosilicate glass; Erbium-doped; Optical properties; Sol-gel method